Complementary and Alternative Medicine Use in a Pregnant Population, Northwest Ethiopia. (9th August 2021) - Emiru, Yohannes Kelifa; Adamu, Betelhem Anteneh; Erara, Melak; Chanie, Tigist; Gurmu, Abyot Endale
Abstract : Background . Complementary and alternative medicine (CAM) appears to be the source of healthcare particularly in the majority of pregnant communities of Africa due to its intrinsic qualities as well as its accessibility and affordability. Despite acknowledged benefits of CAM use in pregnancy, majority of users are unaware of its safety and effects on fetal development. The present study was aimed at examining CAM use among pregnant women in Northwest Ethiopia to provide an opportunity for future investigations on the effectiveness of CAM modalities in the management of pregnancy-related complications across the country. Methods . This was an institution-based cross-sectional study which was conducted at Poly Clinic Health Center in the Northwest part of Ethiopia between March and May 2018. Two hundred and eighty two Ethiopian women were conveniently recruited to take part in the study. Structured questioners were used for the survey. Descriptive statistics of sociodemographic and CAM use characteristics were expressed in frequencies and proportions. Chi-square test was performed to determine the difference between CAM user and nonuser. Besides, binary logistic regression analyses were performed to examine predictors of CAM use in the study population. The result was considered statistically significant if P value ≤ 0.05. Results . The prevalence rate of CAM use in pregnant women was 89.36% with the commonest practice of spiritual healing (65.2%) and herbal supplement (51.8%) CAM therapies. Use of CAM positively associated with marital status and previous number of children. The odds of using CAM among single/not married women were 3.22 times higher (COR: 3.22, CI: 1.07-9.64) as compared to married women. Pregnant women with no children were 3.30 times more likely (COR: 3.30, CI: 0.92-11.84) to use CAM than those women having ≥3 children. Lower odds of using CAM significantly associated with educational level (COR: 0.20, CI: 0.046-0.93) and antenatal care (COR: 0.45, CI: 0.18-1.13) in a binary logistic regression model. Conclusions . A considerable number of pregnant women were utilizing CAM including herbal products as part of their maternity care. This finding provides a reference on the use of CAM for policy-makers, health professionals, and parents. Further studies are needed to investigate the effectiveness and safety of specific CAM modalities with particular focus on herbal medicinal products.